2006
DOI: 10.1093/humupd/dml034
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of tests predicting ovarian reserve and IVF outcome

Abstract: The age-related decline of the success in IVF is largely attributable to a progressive decline of ovarian oocyte quality and quantity. Over the past two decades, a number of so-called ovarian reserve tests (ORTs) have been designed to determine oocyte reserve and quality and have been evaluated for their ability to predict the outcome of IVF in terms of oocyte yield and occurrence of pregnancy. Many of these tests have become part of the routine diagnostic procedure for infertility patients who undergo assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
786
6
127

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,091 publications
(962 citation statements)
references
References 137 publications
17
786
6
127
Order By: Relevance
“…However, when ovarian reserve testing is applied broadly, especially to young women, the potential for a false positive result identifying low ovarian reserve increases and lowers the predictive power of the test, and may be misleading [1,15]. In a recent ASRM committee opinion, the authors concluded that evidence of decreased ovarian reserve does not necessarily equate with inability to conceive, which has a significant amount of literature to support it [15][16][17]. However, the ASRM committee opinion does not discourage the broad use of AMH as there is likely benefit and conclude by stating Bthere is insufficient evidence to recommend that any ovarian reserve test now available should be used as a sole criterion for the use of assisted reproductive technologies^ [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when ovarian reserve testing is applied broadly, especially to young women, the potential for a false positive result identifying low ovarian reserve increases and lowers the predictive power of the test, and may be misleading [1,15]. In a recent ASRM committee opinion, the authors concluded that evidence of decreased ovarian reserve does not necessarily equate with inability to conceive, which has a significant amount of literature to support it [15][16][17]. However, the ASRM committee opinion does not discourage the broad use of AMH as there is likely benefit and conclude by stating Bthere is insufficient evidence to recommend that any ovarian reserve test now available should be used as a sole criterion for the use of assisted reproductive technologies^ [1].…”
Section: Discussionmentioning
confidence: 99%
“…Within the literature, multiple analyses comparing the various ovarian reserve tests have been completed investigating outcomes. Again, no clear consensus was reached [16,18]; however, AMH and AFC appear to be favored within the literature [18][19][20]. Prior researchers have attempted to address the precision, accuracy, and predictive value of AMH in addressing those outcomes, comparing AMH both individually and in combination with other tests.…”
Section: Discussionmentioning
confidence: 99%
“…Basal FSH levels are easy and cheap to obtain and the results require little skill to interpret which makes it an accessible test. However, only extremely elevated results are useful in predicting poor response to ovarian stimulation and non pregnancy [20].…”
Section: Assessing Ovarian Reservementioning
confidence: 99%
“…Thus AMH is emerging as an indirect approximation of age-related NGF populations and rates of recruitment. As such it provides moderate value in prediction of ovarian response in in-vitro fertilization (IVF), however may not be a good predictor of pregnancy [20]. Recently, Bhide et al set out to establish whether there was a link between basal AMH and clinical pregnancy rates in women undergoing IVF/ICSI treatment and attempted to determine a cut off point, below which there are no pregnancies.…”
Section: Assessing Ovarian Reservementioning
confidence: 99%
“…Theca cell function is necessary for normal folliculogenesis and a minimal threshold level of LH is needed for theca cell stimulation and production of androgens to improve folliculogenesis, as was demonstrated in hypogonadotropic hypogonadism patients [31]. Several tests that examine granulosa cell function were developed to evaluate ovarian reserve before ART: day 3 FSH, day 3 estradiol, inhibin B, CCCT, EFORT, and GAST [32]. Most of these tests have shown only a modest predictive value and consequently, have not gained wide clinical acceptance and application.…”
Section: Discussionmentioning
confidence: 99%